2022
DOI: 10.1002/smll.202205960
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐Level Information Encryption/Decryption of Fluorescent Hydrogels Based on Spatially Programmed Crystal Phases

Abstract: The growing urgence of information protection promotes continuously the development of information‐encryption technique. To date, hydrogels have become an emerging candidate for advanced information‐encryption materials, because of their unique stimulus responsiveness. However, current methods to design multi‐level information‐encrypted hydrogels usually need sophisticated chemistry or experimental setup. Herein, a novel strategy is reported to fabricate hydrogels with multi‐level information encryption/decryp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…In addition, the micropillars show the potential of two‐level information encryption/decryption. [ 38 ] For example, by setting a two‐level magnetic field in which each level corresponds to a kind of magnetized micropillar with no deformation occurring, the combination between two patterns could be displayed and switched quickly on a single magnetic micropillar array (Figure S9, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the micropillars show the potential of two‐level information encryption/decryption. [ 38 ] For example, by setting a two‐level magnetic field in which each level corresponds to a kind of magnetized micropillar with no deformation occurring, the combination between two patterns could be displayed and switched quickly on a single magnetic micropillar array (Figure S9, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…This bionic multilayer structure is designed for encryption and decryption by solvent substitution and temperature switching. Yu and co-workers proposed an innovative strategy to prepare hydrogels with multilevel information encryption/decryption capability by spatially programming the polycrystalline phases . The homocrystalline (HC) and stereocomplex (SC) crystalline phases in the fluorescent hydrogels were tuned by solvent-assisted diffusion and solvent exchange.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Applications of luminescent materials in the fields of anti-counterfeiting technology, optical information storage, and optical information encryption (OIE) have attracted increasing attention due to the multimodality protection mechanisms, including luminescent intensity, emission wavelength, lifetime, and patterns. Outstanding examples have been demonstrated, [5][6][7][8] including fluorescent organic dyes, [9,10] quantum dots (QDs), [11,12] hydrogels, [13][14][15] carbon dot (CDs), [16][17][18] and organic phosphorescent materials. [19][20][21] For instance, Nagarkar et al demonstrated wavelength multiplexing by printing dye molecules with seven different emissions, which could represent eightbit binary numbers at each pixel.…”
Section: Introductionmentioning
confidence: 99%